2019
DOI: 10.1111/1556-4029.14205
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Effectiveness of Noncontact Three‐Dimensional Surface Scanning for the Assessment of Open Injuries

Abstract: Noncontact three‐dimensional (3D) surface scanning methods are used within forensic medicine to record traumas and other related findings. A structured light scanning technique is one of these methods and the most suitable for the forensic field. An assessment of the efficiency of different structured light scanners with forensic injuries is essential to validate this technique for wound documentation. The purpose of this study was to evaluate the capability of the HP structured light scanner Pro S3 for digiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The advantages of 3D reconstruction methods over photography in documenting and presenting injuries are already demonstrated [ 31 , 32 ]. Photogrammetry allows creating 3D textured surface models from a series of overlapping photographs taken from varying viewpoints [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of 3D reconstruction methods over photography in documenting and presenting injuries are already demonstrated [ 31 , 32 ]. Photogrammetry allows creating 3D textured surface models from a series of overlapping photographs taken from varying viewpoints [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional surface scanning (3DSS) has the ability to collect data from various directions/angles without physically handling [ 41 ]. Previous work has demonstrated that this approach to recording and analysing human remains is superior to 2D and photogrammetric methods [ 9 , [42] , [43] , [44] , [45] , [46] , [47] ].…”
Section: Discussionmentioning
confidence: 99%
“…examination of fragile and otherwise inaccessible material, the production of affordable, high-quality replicas for display, teaching, and research, increased accuracy and enhanced data sharing [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , 17 , 18 ]. The use of surface scanning in forensic anthropology and medicine has been well established [ 19 ], in contexts such as the analysis of burned remains [ 20 ], replication of anthropological specimens for curation and illustration [ 20 ], recording taphonomic changes [ 21 ], evaluating trauma [ 1 , 22 ], determining bullet pathways [ 23 ], and presenting evidence in court [ [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%